Main International Legal Regimes during an Armed Conflict - N. V. Ostroukhov (Московский журнал международного права, 2009)
The article deals with major international legal regimes that are used by the warring sides during an armed conflict. International legal regime is an international law determined set of rules regulating the activities of the states, their government institutions and officials, as well as the order of exercising their rights and duties in the context of securing and maintaining a state sovereignty, defence, national security and implementation of international commitments. The common target and main designation of their international legal regimes are mostly aimed at setting up legal and managerial barriers that would hamper and eliminate violation of legal establishments.The author gives special survey to the research of such international legal regimes as military occupation, war imprisonment, internment, medical staff activities, and protection of the civilians.